Medical Image Computing and Computer Assisted Intervention - MICCAI 2020 : 23rd International Conference, Lima, Peru, October 4-8, 2020, Proceedings, Part VII /: 23rd International Conference, Lima, Peru, October 4-8, 2020, Proceedings, Part VII. (2020) - Unknown
No abstract available